THE SIGNIFICANCE OF PATHOLOGY IN NURSING PRACTICE - Sadulloeva Mashkhura Adizovna; Rajabova Rokhila Bakhshullovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Pathology,  the  study  of  diseases  and  their  processes, holds  critical importance in the field of nursing. For nursing professionals, a solid understanding of pathology enhances patient assessment, aids in the identification of disease processes, and informs the provision of evidence-based care. This article explores the relevance of  pathology  in  nursing  education  and  practice,  emphasizing  its  role  in  improving patient outcomes.